A review of the ESL/EFL learners’ gains from online peer feedback on English writing - Cao, Siyi; Zhou, Siruo; Luo, Yong; Wang, Tao; Zhou, Tongquan; Xu, Yizhong (Frontiers in Psychology, 2022)
Peer feedback plays an essential role in English as a Second/Foreign Language (ESL/EFL) writing. Traditionally, offline PF was more widely favored but nowadays online peer feedback (OPF) has become a frequent practice in ESL/EFL learners’ daily writing. This study is undertaken to probe into the gains of using OPF in ESL/EFL writing on the basis of 37 research articles published in core journals from 2012 till 2022. In order to document the previous researches, we capitalize on three methods to evaluate and analyze the data, i.e., database search, citation search and manual search. Results show that from the perspective of the ESL/EFL learners’ gains, the OPF was basically divided into two categories (cognitive OPF and meta-cognitive OPF), involving nine aspects in all: face-based strategies, revision-based comments, writing efficiency, overall writing quality, learning environment, reflection/critical thinking/ responsibility, writing emotion, motivation, and attitudes; and the corresponding nine gains could be well explained by a set of theories like process-oriented writing approach, Vygotsky’s socio-cognitive theory of learning, collaborative learning theory, interactionist theory of L2 acquisition, Choice Theory, Group Dynamics Theory and Constructive Learning Theory. By comparison, the gains from OPF outperformed those from offline PF in many dimensions (e.g., face-based strategies), despite some overlaps (e.g., the shift of the role) revealed in a couple of investigations. Based on the past studies, we propose some pedagogical implications on OPF from ESL/EFL writing, including accenting the “student-centered” teaching strategy, providing students with OPF on the basis of incremental knowledge, adopting OPF regularly in ESL/EFL study to shape personalities and outlooks and puting into its full play with recourse to abundant internet-based vehicles. This review is desired to provide a guideline for both the peer feedback practice and the upcoming scholarly researches with respect to EFL/ESL writing.